Uni- and Bi-directional Er3+-doped fiber soliton laser mode-locked by GIMF-based SA. (February 2023) - Huang, Song; Wang, Zhaokun
Highlights: The bidirectional mode locking and the quasi-unidirectional mode locking is realized in an Er-doped fiber laser. The bidirectional operations could show different soliton state of the forward conventional solitons and backward bound solitons. A record pulse energy of 1.12 nJ at the pump power of 430 mW is achieved. Abstract: In this paper, we have experimentally demonstrated an ultrafast Er-doped fiber laser mode-locked by the GIMF-based saturable absorber without an optical isolator for various soliton behaviors. The adjustment of the polarization controller results in different losses for the counter-propagating lasers. And thus, not only the bidirectional solitons, but also the quasi-unidirectional solitons are realized. For the bidirectional operation, the counterpropagating conventional solitons with the pulse energy of >1.12 nJ demonstrates different central wavelengths, repetition rates, and pulse widths. For the unidirectional operation, the laser operates in either the clockwise or the counter-clockwise directions with an emission strengths difference of larger than 31 dB. Interestingly, the bidirectional operations could show different soliton state of the forward conventional solitons and backward bound solitons. Our research would be beneficial for the further understanding of the formation and transformation of the bidirectional solitons and can find vital applications in gyroscopic and other dual-channel applications.